Hydrogen Evolution from Water in Presence of Diethylamine Acetate and 1-Butyl-3-methyl Imidazolium Tetrafluoroborate Ionic Liquids as Electrocatalysts on Different Electrode Materials - Long, L.Q.; Hung, H.D.; Ha, V.T.T.; Yen, P.T.H.; Phong, P.H.; Hung, L.Q. (Asian Journal of Chemistry, 2014)
This report presents the investigation of electrochemical generation of hydrogen from water in the presence of the ionic liquids diethylamine acetate ([DEA][Ac]) and 1-butyl-3-methyl imidazolium tetrafluoroborate ([BMIM][BF4]) on different electrode materials such as brass, stainless steel, carbon steel and carbon nanotube paste. Electrochemical properties were investigated using cyclic voltametric, potentiostatic and galvanostatic techniques. The best concentration in water of both ionic liquids studied was obtained at 10 vol. % in cases of brass and stainless steel and for CT3 in solution containing [DEA][Ac]. Efficiencies of hydrogen evolution were determined to be between 94 and 99 %. The materials displayed high stability during the electrolysis process, especially for stainless steel.